(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
This paper proposes an easy method based on wavelet networks for modeling the Bit Error Rate over a Rayleigh multipath fading channel taking care of a power control error. The RAKE receiver is considered for both coherent and non-coherent reception in this work when using a Weighted Despreading sequences for MAI cancellation in MC/DS-CDMA. It shows that the wavelet networks give a good reduction in term of complexity when calculating BER.